Review of the Book: Itihaser Pata Theke - Vol I & II - Kishore, Dr Jugal (Journal of Advanced Research in English & Education, 2022)
The book is the compilation of summaries of 21 lecture delivered virtually by eminent scholars for the participants from all over the globe between June and December 2021.